2022
DOI: 10.1039/d2ce00627h
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-induced phase transformations of ZIF-L to ZIF-8 and their derivatives' gas-sensing properties

Abstract: Detailed study of topological phase transition is essential in guiding the controlled synthesis of materials. Herein, a series of zeolitic-imidazolate frameworks (ZIFs) and derived metal oxide with tailored morphologies and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Metal–organic frameworks (MOF) are formed via coordinate bonding between organic linkers and metal ions. MOFs synthesized using a variety of materials and exhibiting versatile functionalities have been applied in environmental science, sensor separation, catalysis, and drug delivery. However, MOFs used for drug delivery and their building blocks should be biodegradable . For example, sugars such as starch and lactose are safe and biodegradable.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOF) are formed via coordinate bonding between organic linkers and metal ions. MOFs synthesized using a variety of materials and exhibiting versatile functionalities have been applied in environmental science, sensor separation, catalysis, and drug delivery. However, MOFs used for drug delivery and their building blocks should be biodegradable . For example, sugars such as starch and lactose are safe and biodegradable.…”
Section: Introductionmentioning
confidence: 99%
“…The high ratio of Hmim/Zn 2+ in the aqueous solution facilitated the formation of ZIF-8, while the low ratio was beneficial to the growth of ZIF-L. Some studies showed that ZIF-L can even be transformed into ZIF-8 through some topological phase transition under the condition of a high temperature organic solvent. All these studies seem to imply that an aqueous solution and a low ratio of Hmim to Zn 2+ in the aqueous solution are two necessary conditions for the synthesis of ZIF-L.…”
Section: Introductionmentioning
confidence: 99%